Epidemiological Study of Burn Deaths at a Tertiary Care Centre in Mumbai - Babaso Kalel1 , Pawan Sabale2 , Shailesh Mohite3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Death due to burns is an important cause of unnatural death commonly encountered in Medico-legal Practice.This prospective study was conducted on 100 cases of burn deaths caused by flames, hot liquids and flashof electricity. This study was conducted to know the demographic profiles, common risk factors, causes andmanners of death in fatal cases of burns. Most of the cases were in the age group of 21 to 50 years with apeak incidence in 21-30 years age group, with female predominance. In the study, maximum cases were dueto kerosene stove blast leading to accidental burns, followed by pouring of kerosene as a source of burn..